الكمون الاجتماعي للرجل في البناء الثقافي للمجتمع الجزائري وأثره على المكانة الاجتماعية للمرأة العاملة خارج البيت - بلبلدي, يوسف; نويصر, بلقاسم (جامعة الوادي - University of Eloued, 2021)
ملخص: تمثل المرأة الجزائرية نصف الخارطة السكانية في الجزائر كما تمثل نسبة لا يستهان بها في سوق العمل، فقد غزت العديد من المجالات وتقلدت الوظائف والمناصب في مختلف المستويات، هذا في مجتمع تتجدر فيه فكرة قوة الرجل وضعف الأنثى، فالثقافة السائدة في المجتمع والتي يتصرف كل طرف حيال الطرف الأخر بناءا على معطياتها تزخر بمسوغات فكرية تكرس ارتقاء الرجل ودونية المرأة، وقد انعكس هذا الواقع على المكانة الاجتماعية التي تتبوؤها المرأة وخاصة العاملة خارج البيت في المجتمع. في هذا البحث سنحاول الكشف عن واقع المكانة الاجتماعية للمرأة الجزائرية العاملة خارج البيت وتأثير الثقافة الذكورية السائدة في المجتمع عليها. Abstract: The Algerian women represents half of the population in Algeria and a significant part of the labor market. She has invaded many fields and assumed jobs and positions at various levels in a society where the idea of male power and female weakness is rooted. The prevailing culture in the society on the basis of which the other party acts is charged with intellectual grounds that enshrine the ascension of men and the inferiority of women. This reality has been reflected in the social status of women in society, especially those working outside the home. In this research, we will try to reveal the reality of the social status of the Algerian women working outside the home and the impact of mal culture prevailing in society
مقال
Keywords: الكمون الاجتماعي ؛ الرجل ؛ البناء الثقافي ؛ المرأة العاملة ؛ المجتمع; The Social Potential; men ; cultural construction; working women; society